Sanctions on Russia, Aid to Ukraine, and Energy for Germany - Teodora Boneva; Armin Falk; Mark Fallak; Lasse Stötzer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
According to a representative briq survey, more than two-thirds of the German population would support a halt to energy imports from Russia in order to increase pressure on the Russian government. A broad majority would also welcome additional measures to reduce energy dependence, including alternative energy sources and energy-saving. When it comes to helping the Ukrainian people, many of the respondents would support both aid and integration policies, including permanent residence and work permits for refugees. Germans are divided, however, on the question of further arms deliveries to Ukraine.
Keywords: 330